Réponses

2013-05-02T16:25:04+02:00

a=axa+ax5+7xa+7x5

a=a²+5a+7a+35

a=a²+12a+35

 

b=x x x+x x 5-4 x x-4x5

b=x²+5x-4x-20

b=x²+x-20

 

c=-x x9+ x x x+3x9-3 x x

c=-9x+x²+27-3x

c=x²+6x+27

 

d=-x x 5 + x x x -1x5 + 1 x x

d= -5x + x² - 5 +1x

d=x²-4x-5

2013-05-02T16:29:53+02:00

a= (a+7)(a+5)

  = a*a+a*5+7*a+7*5

  = 2a² +5a +7a +35

  = 2a² +12a +35

 

b=(x-4)(x+5)

  = x*x +x*5 -4*x-4*5

  = 2x² + 5x - 4x -20

  = 2x²  + x - 20

 

c=(-x+3)(9-x)

  =( - x*9) - (-x*x) + 3*9-3*x

  =  -9x +2x² + 27 -3x

  = 2x² -12x +27

 

d=(-x-1)(5-x)

  = (-x*5)-(x*-x) -1*5 +x

  = -5x +2x² -5+x

  = 2x²-4x -5